2013
DOI: 10.5007/2175-7925.2013v26n1p37
|View full text |Cite
|
Sign up to set email alerts
|

Adubação orgânica em tomateiros do grupo cereja

Abstract: ResumoO tomate cereja (Solanum lycopersicum) é altamente exigente em relação aos nutrientes minerais. O uso do esterco animal mostra-se uma forma eficiente e sustentável de adubação para essa cultura. O objetivo deste trabalho foi avaliar o efeito de diferentes doses de esterco bovino no crescimento vegetativo e reprodutivo do tomate cereja. O experimento foi conduzido em casa de vegetação do Departamento de Fitotecnia da Universidade Federal de Viçosa, sendo utilizando delineamento experimental inteiramente c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 2 publications
1
5
0
2
Order By: Relevance
“…The treatments with organic and chemical fertilizer provide larger diameters due to being rich in potassium that promotes increase in diameter, being one of the most required elements especially for performing the functions of carbohydrate translocation and regulation of stoma opening and closing. Potassium still influences tissue formation and plant respiration processes, increasing sugar content, size, weight and resistance to fruit handling (Maia et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The treatments with organic and chemical fertilizer provide larger diameters due to being rich in potassium that promotes increase in diameter, being one of the most required elements especially for performing the functions of carbohydrate translocation and regulation of stoma opening and closing. Potassium still influences tissue formation and plant respiration processes, increasing sugar content, size, weight and resistance to fruit handling (Maia et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…For water depths, decimal fraction and five levels of crop evapotranspiration -ETc (Fraction (F) of 70%, 85%, 100%, 115% and 130% of the ETc) were used for the water depths. For fertilization type factor, three types were used: no fertilized soil (Control), NPK fertilized soil (Chemical fertilization: Urea, Simple Superphosphate and Potassium Chloride) based on the recommendations of Novais et al (2007) and fertilized with earthworm humus (Organic Fertilization) based on the recommendation of Maia et al (2013), with five replications, totaling 75 experimental plots.…”
Section: Methodsmentioning
confidence: 99%
“…According to Fan et al (2018), phosphorus is an important nutrient for root growth and plays a critical role in plant metabolism. Maia et al (2013) investigated the effect of organic fertilization on cherry tomato plants and found higher phosphorus levels in plants treated with a mix of soil and cattle manure. Similarly, the highest phosphorus concentration was observed under the lower manure proportion.…”
Section: Leaf Mineral Compositionmentioning
confidence: 99%
“…Several authors have reported the influence of organic fertilization on the mineral composition of tomato leaves. Maia et al (2013) found that the macro-and micronutrient contents in cherry tomato leaves under different doses of cattle manure compared to the chemical fertilization were influenced by the addition of the organic fertilizer to the contents of N, P, K, Ca, Mg, S, Mn and Zn.…”
Section: Leaf Mineral Compositionmentioning
confidence: 99%
“…Ainda assim, a adubação orgânica é suficiente para que produza bem, pois se adapta bem às condições de diferentes solos, podendo ser irrigado, inclusive, com águas de diferentes salinidades sob tais circunstâncias. O uso de efluentes de peixes, esterco bovino e outros adubos orgânicos podem incrementar a produtividade do tomateiro(MAIA et al, 2013). A produção do tomate cereja depende diretamente da matéria orgânica ofertada às mudas e da luz solar ENDUT et al, 2009).…”
unclassified